Social and physical factors influencing the use and consumption of European fabric by nineteenth century indigenous societies in the old Transvaal - Dymond, Scarlett Miranda (My University, 2012)
In 1854 friction over labour practices, land appropriation and inland trade routes led to the simultaneous murder of three groups of Dutch settlers, or Trekkers by the Kekana Ndebele. The Trekkers mounted a retaliatory attack on the Kekana, who retreated into Historic Cave, Limpopo Province. Although the cave had been well stocked prior to the attack, the Kekana were decimated and this event later became known as the Siege of Makapan. Excavations from 2001 uncovered a unique cache of European fabric preserved by the unusually dry conditions in the cave. Within the fluid social and political landscape of the internal frontier of nineteenth century northern Transvaal, European clothing and fabric was a valuable resource that served different functions. Contemporary records from traders, travellers and missionaries indicate that, as a high status item, clothing and fabric was often restricted to elites, was subject to social mores and could be used to signal changing religious or political affiliations. Certain groups, or individuals, also invested fabric with unusual properties. No entire garments were recovered from Historic Cave but some of the fragmentary fabric remains that were revealed indicate their possible use as ritual objects endowed with supernatural qualities. The unique find from Historic Cave allows an opportunity of comparing archaeological remains with historical documents to understand more about fabric use at this time.
M.Sc., Faculty of Science, University of the Witwatersrand, 2011
Keywords: Archaeology; Dyes and dyeing; Textile fabrics